Preparation method of high-performance catalytic electrode material for hydrogen production by electrolysis of water and catalytic electrode material
By doping Ce elements on the Ni-Fe electrode and providing oxygen vacancy with Ce's redox pairs, the performance degradation caused by Fe precipitation in the electrolytic water reaction of Ni-Fe catalyst is solved, and the activity and stability of the electrode are significantly improved, achieving efficient conversion of electrical energy into hydrogen energy.
Patent Information
- Application Number
- CN202411924945.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-18
AI Technical Summary
The existing Ni-Fe catalysts have deteriorated electrode performance due to the precipitation and dissolution of Fe in the electrolytic water reaction, and the activity of simple Ni(OH)2 decreases and structural unstable during long-term electrolysis.
By doping Ce elements on the Ni-Fe electrode, oxygen vacancies are provided using Ce redox pairs to provide them, improving the catalytic performance and stability of the electrode. The performance of the NiFeCe electrode is optimized by changing the ratio of deposition voltage and Ce.
It significantly improves the activity and stability of the electrode, reduces the overpotential required for the reaction, improves the efficiency of converting electrical energy into hydrogen energy, reduces energy consumption, and speeds up the process of electrolytic water reaction.
Smart Images

Figure CN119843310A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalytic electrode materials, and in particular to a preparation method of a high-performance catalytic electrode material for producing hydrogen by electrolysis of water and the catalytic electrode material. Background Art
[0002] Water electrolysis is an effective means of converting electrical energy into chemical energy. Water electrolysis can decompose water into hydrogen and oxygen without producing other pollution, and has important application value in the field of renewable energy. Hydrogen energy, as a clean energy, is of decisive significance for achieving energy structure transformation and alleviating environmental problems. Water electrolysis undergoes water oxidation reaction (OER) at the anode to generate oxygen, and reduction reaction (HER) at the cathode to generate hydrogen. The OER reaction process requires the transfer of 4e - , is a process with very slow kinetics, and a very high overvoltage is required to drive the reaction. In the OER reaction, the introduction of catalysts helps to reduce the overpotential, thereby improving the energy conversion efficiency.
[0003] Nickel-based catalysts are considered to be very promising choices due to their good catalytic performance, abundant resources and low cost. In recent years, layered nickel hydroxide (Ni(OH)2) has been widely studied as an electrode material due to its excellent electrochemical performance and stability. However, pure Ni(OH)2 still faces the challenges of decreased activity and structural instability during long-term electrolysis. Under alkaline conditions, NiFeO x H y It is considered to be the most active electrocatalyst for OER. After Fe-doping Ni(OH)2, two obvious phenomena will occur: Ni(OH )2 / The redox peak of NiOOH will shift toward the positive potential; the activity of the catalyst will be significantly improved. However, the performance of the Ni-Fe electrode will decrease due to the precipitation and dissolution of Fe in the ordinary Ni-Fe catalyst during the reaction. Therefore, it is very important to solve the precipitation problem of active elements. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing a high-performance catalytic electrode material for hydrogen production by electrolysis of water and a catalytic electrode material in order to overcome the defects of the above-mentioned prior art, and to improve the catalytic performance and stability of the electrode by providing a large number of oxygen vacancies by the redox couple of Ce. The performance optimization of the NiFeCe electrode is achieved by changing the deposition voltage and the ratio of Ce. The method is suitable for preparing electrodes for efficient water electrolysis reaction. The incorporation of Ce metal can well promote the OER reaction and the formation of oxygen, thereby accelerating the process of water electrolysis reaction.
[0005] The purpose of the present invention can be achieved by the following technical solutions:
[0006] The first aspect of the present invention provides a method for preparing a high-performance catalytic electrode material for hydrogen production by electrolysis of water, comprising the following steps:
[0007] S1. Substrate pretreatment: pretreating the conductive substrate to remove surface impurities;
[0008] S2. Preparation of electroplating solution: prepare an electroplating solution including a nickel source, a pore-forming agent, an iron source, and a cerium source, wherein the nickel source is a nickel salt compound providing nickel ions, and the concentration is in the range of 0.1M to 1M, the pore-forming agent is a compound that generates gas to assist pore formation during electrolysis, and the concentration is in the range of 0.5M to 4M, the iron source is a ferric salt compound providing ferrous ions, and the concentration is in the range of 0.1M to 0.5M, and the cerium source is a cerium salt compound providing cerium ions, and the concentration is in the range of 0.1M to 0.5M;
[0009] S3, electrodeposition process: using the electroplating solution obtained in S2, the pretreated conductive substrate is used as a cathode, another conductive material is used as an anode, and electrodeposition conditions are applied by a power supply to perform electrodeposition;
[0010] S4, post-treatment: After the electrodeposition is completed, the electrode is taken out from the electrolyte, rinsed with a cleaning solution to remove the residual electrolyte on the surface, and then dried;
[0011] S5. Sintering process: Sintering the electrode under a protective atmosphere to obtain a high-performance catalytic electrode material for hydrogen production by electrolysis of water.
[0012] Furthermore, in S1, the pretreatment includes sequentially using an acid solution ultrasonic cleaning, deionized water ultrasonic cleaning, and anhydrous ethanol ultrasonic cleaning, and then drying.
[0013] Furthermore, in S2, the nickel source is one of nickel sulfate, nickel nitrate and nickel chloride.
[0014] Furthermore, in S2, the pore-forming agent is ammonium chloride, which is used to form a bubble template to achieve pore formation.
[0015] Furthermore, in S2, the iron source is ferrous chloride, and the cerium source is cerium chloride or cerium nitrate.
[0016] Further, in S3, when the three elements Ni, Fe, and Ce are deposited in one step, during the electroplating process, the pretreated nickel mesh is used as a cathode, connected to a negative power supply, and a nickel rod is used as an anode, connected to a positive power supply, and a constant voltage is applied by the power supply for electroplating, the applied voltage is 1V to 10V, the electroplating time is controlled at 5 to 30 minutes, and the temperature is controlled at 20°C to 60°C;
[0017] The electroplating solution is a mixed electroplating solution prepared with a nickel source, a pore-forming agent, an iron source, and a cerium source according to a preset concentration;
[0018] When depositing the three elements Ni, Fe, and Ce in one step, the mixed electroplating solution of the nickel source, pore former, iron source, and cerium source needs to be stirred evenly and left to stand for 10-30 minutes after preparation to ensure that each component is fully dissolved and evenly dispersed.
[0019] Further, in S3, when a two-step deposition method is adopted to introduce only Ce element on the surface of the nickel-iron porous electrode, the electrodeposition process includes:
[0020] In the two-step deposition, when the nickel-iron porous electrode is only introduced with the Ce element on the electrode surface, the following steps are included:
[0021] 1) Preparation of nickel-iron electrode substrate:
[0022] During the electrodeposition process, the pretreated nickel mesh is used as the cathode and connected to the negative power supply; the nickel rod is used as the anode and connected to the positive power supply. A constant current is applied through the power supply for electrodeposition, and the current density is 0.5A / cm 2 Up to 2A / cm 2 , the electrodeposition time is controlled within 5 to 30 minutes, and the temperature is controlled within 20°C to 60°C;
[0023] The electroplating solution is a mixed electroplating solution containing a nickel source, a pore-forming agent, and an iron source prepared at a preset concentration;
[0024] 2) Deposition of nickel-iron-cerium on a nickel-iron substrate:
[0025] During the electroplating process, the pretreated nickel mesh is used as the cathode, connected to the negative power supply, and the nickel rod is used as the anode, connected to the positive power supply. A constant voltage is applied by the power supply for electroplating, and the applied voltage is 1V to 10V. The electroplating time is controlled within 5 to 30 minutes, and the temperature is controlled within 20°C to 60°C.
[0026] The electroplating solution is a mixed electroplating solution prepared by a nickel source, a pore-forming agent, an iron source and a cerium source according to a preset concentration, wherein the nickel source is one of nickel sulfate, nickel nitrate or nickel chloride.
[0027] Furthermore, in S3, during the preparation of the nickel-iron electrode substrate, the electroplating solution used must first be prepared to completely dissolve the nickel source and the pore-forming agent, and then the iron source is added and continuously stirred until the solution is clear and transparent.
[0028] Furthermore, in S3, during the deposition of nickel-iron-cerium on the nickel-iron substrate, the electroplating solution is continuously stirred during the electrodeposition process at a stirring speed of 200-500 rpm to ensure uniformity of the electrodeposition.
[0029] The second aspect of the present invention provides a high-performance catalytic electrode material prepared by the above method, wherein the catalyst improves the catalytic performance and stability of the electrode through a large number of oxygen vacancies provided by the Ce redox couple, promotes the OER reaction and the formation of oxygen, thereby accelerating the process of hydrogen production by electrolysis of water.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] 1) By doping metal Ce on the Ni-Fe electrode and introducing the Ce redox couple, the abundant oxygen vacancies greatly improve the activity and stability of the electrode. This enables the electrode to catalyze the reaction more efficiently during the electrolysis of water, reduces the overpotential required for the reaction, improves the efficiency of converting electrical energy into hydrogen energy, effectively reduces energy consumption, and provides a more economical technical solution for large-scale electrolysis of water to produce hydrogen.
[0032] 2) The introduction of Ce element not only does not increase the number of active sites, but can significantly improve the activity of a single active site. In the oxygen evolution reaction (OER) of water electrolysis, this optimization effect makes oxygen formation more rapid, greatly speeds up the water electrolysis reaction process, increases the hydrogen production rate, and enhances the hydrogen production capacity of the overall water electrolysis hydrogen production system.
[0033] 3) The present invention provides two preparation methods for nickel-iron porous electrodes: one-step deposition of three elements Ni, Fe, and Ce and two-step deposition of only Ce elements introduced on the electrode surface. The one-step deposition method is relatively simple and quick to operate, and an electrode material with good performance can be prepared in a short time; the two-step deposition method can more accurately control the structure and composition of the electrode, first prepare the nickel-iron electrode substrate, and then introduce the Ce element on its surface, which is conducive to further optimizing the performance of the electrode, meeting different production requirements and process conditions, and improving the adaptability and operability of the present invention in practical applications.
[0034] 4) The plating solution used in the preparation process contains a pore-forming agent, such as ammonium chloride, which decomposes during the electrolysis process to produce hydrogen to form a bubble template. The porous self-supporting electrode structure finally prepared has a large specific surface area. This porous structure is conducive to the diffusion of electrolytes and the transmission of gases, further improving the catalytic performance of the electrode, reducing mass transfer resistance, allowing the reaction to proceed more smoothly, and improving the overall reaction kinetics.
[0035] 5) Compared with the traditional nickel-iron electrode preparation method, the present invention determines the optimal co-deposition potential of nickel, iron and cerium elements by precisely controlling the electrodeposition process, thereby achieving a significant improvement in electrode performance without increasing excessive costs and complex processes. It shows stronger competitiveness in the field of hydrogen production by electrolysis of water and is expected to promote the further development of technology in this field and the expansion of its application. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 : NiFeCe electrodes prepared by one-step deposition at different deposition voltages;
[0037] Figure 2 : SEM and EDS images of the electrode deposited in one step. Among them: 1 is the SEM image of the electrode after one step deposition, 2 is the distribution of Fe elements in the EDS image, 3 is the distribution of Ni elements in the EDS image, and 4 is the distribution of Ce elements in the EDS image.
[0038] Figure 3 : Performance curve of electrode. DETAILED DESCRIPTION
[0039] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. Component models, material names, connection structures, control methods, algorithms and other features not clearly described in this technical solution are all considered to be common technical features disclosed in the prior art.
[0040] Embodiment 1:
[0041] One-step deposition method
[0042] Step 1: Substrate Preparation
[0043] A) The nickel mesh substrate was ultrasonically cleaned in 1 M dilute hydrochloric acid, deionized water, and anhydrous ethanol for 15 minutes to remove surface impurities.
[0044] B) The cleaned nickel mesh substrate is placed at the working electrode position and waits for further processing.
[0045] Step 2: Electrodeposition of Porous NiFeCe Electrode
[0046] A) An electrodeposition solution containing 0.5 M NiCl2, 1 M NH4Cl, 0.2 M FeCl2 and 0.2 M CeCl3 was prepared in an electrodeposition tank, and then the solution was thoroughly mixed by nitrogen ventilation.
[0047] B) A clean nickel mesh substrate was placed in an electrodeposition bath and used as a working electrode.
[0048] C) Applying a deposition voltage of 3 V and continuing the electrodeposition for 10 minutes to form a porous nickel-iron-cerium electrode.
[0049] D) Remove the electrode, rinse with deionized water and ethanol, and dry.
[0050] Step 3: Sintering Process
[0051] A) The prepared electrode was placed on a mesh belt furnace, the sintering temperature was set to 1000°C, the sintering time was set to 1 s, and nitrogen was used as the protective atmosphere.
[0052] B) Place the electrode into a preheated 1000°C mesh belt furnace to ensure instant sintering.
[0053] C) After sintering, the electrode is taken out of the furnace after cooling to room temperature, and then washed with deionized water and dried.
[0054] Step 4: Performance Evaluation:
[0055] A) Material Characterization
[0056] Morphology observation: Scanning electron microscopy (SEM) was used to evaluate the changes in the surface morphology of the material and observe the morphology changes caused by cerium doping.
[0057] Surface analysis: The electrode surface is analyzed using energy dispersive X-ray spectroscopy (EDS) to confirm the successful introduction of the target elements and their chemical state.
[0058] B) Performance Evaluation:
[0059] The test was performed using a three-electrode system, with the electrode prepared in this example as the working electrode, the mercuric oxide electrode as the reference electrode, and the graphite electrode as the counter electrode.
[0060] The test was carried out in a 1M KOH aqueous solution. The electrolyte was fully saturated with oxygen before the test to ensure that the oxygen concentration in the electrolyte was constant during the test.
[0061] Linear Sweep Voltammetry (LSV) Test:
[0062] LSV tests were performed to evaluate the oxygen evolution reaction (OER) activity of the materials at a scan rate of 5 mV / s in the range of 0 V to 0.8 V vs. mercuric oxide.
[0063] Figure 1 Electron micrographs of NiFeCe electrodes prepared by one-step deposition at different deposition voltages (1.5V, 2V, 3V, 4V). It can be seen that when the applied voltage increases, the electrode begins to form a porous structure and the electrochemically active area increases.
[0064] Figure 2 The SEM and EDS images of the electrode deposited in one step. Among them: 1 is the SEM image of the electrode after one-step deposition, 2 is the distribution of Fe elements in the EDS image, 3 is the distribution of Ni elements in the EDS image, and 4 is the distribution of Ce elements in the EDS image. The three elements are evenly distributed in the electrode.
[0065] Electrode performance test LSV curve Figure 3 As shown, it can be seen that after the introduction of Ce element, the electrode performance is greatly improved.
[0066] Embodiment 2:
[0067] Two-step deposition method
[0068] Step 1: Substrate Preparation
[0069] A) The nickel mesh substrate was ultrasonically cleaned in 1 M dilute hydrochloric acid, deionized water, and anhydrous ethanol for 15 minutes to remove surface impurities.
[0070] B) The cleaned nickel mesh substrate is placed at the working electrode position and waits for further processing.
[0071] Step 2: Electrodeposition of porous nickel-iron substrate
[0072] A) An electrodeposition solution containing 0.5 M NiCl2, 1 M NH4Cl, and 0.2 M FeCl2 was prepared in an electrodeposition tank, and then the solution was thoroughly mixed by nitrogen ventilation.
[0073] B) A clean nickel mesh substrate was placed in an electrodeposition bath and used as a working electrode.
[0074] C) Apply 2A / cm 2 The current density was 2.50 and the electrodeposition was continued for 10 min to form a porous Ni-Fe substrate.
[0075] D) Remove the electrode, rinse with deionized water and ethanol, and dry.
[0076] E) This step can be selected to perform sintering or not, so that there is one sintering or two sinterings in the preparation process, and the influence of the sintering process can be judged by this. The sintering temperature is set to 1000°C, the sintering time is 1s, and nitrogen is used as the protective atmosphere.
[0077] Step 3: Depositing nickel-iron-cerium elements on nickel-iron substrate
[0078] (1) Traditional electrodeposition method
[0079] A) An electrodeposition solution containing 0.5 M NiCl2, 1 M NH4Cl, 0.2 M FeCl2 and 0.5 M CeCl3 was prepared in an electrodeposition tank, and then the solution was thoroughly mixed by nitrogen ventilation.
[0080] B) A clean nickel mesh substrate was placed in an electrodeposition bath and used as a working electrode.
[0081] C) A deposition voltage of 3 V was applied and the electrodeposition was continued for 10 minutes to form a porous nickel-iron-cerium electrode.
[0082] D) Remove the electrode, rinse with deionized water and ethanol, and dry.
[0083] (2) Pulse electrodeposition method
[0084] A) An electrodeposition solution containing 0.5 M NiCl2, 2 M NH4Cl, 0.2 M FeCl2 and 0.2 M CeCl3 was prepared in an electrodeposition tank, and then the solution was thoroughly mixed by nitrogen ventilation.
[0085] B) A clean nickel mesh substrate was placed in an electrodeposition bath and used as a working electrode.
[0086] C) Using AC power as the deposition power source, the deposition process is a cycle of multiple pulse modes, one of which includes: ① voltage value 0, time 0.1s, slope 0.1s; ② voltage value 1V, 2V, 3V, 4V, 5V, time 0.2s, slope 0.1s; ③ voltage value 0, slope 0.1s, time is set to 0.1s, 1s, 2s, 3s. That is, the on time is fixed to 0.2s, and the off time is 0.1s, 1s, 2s, 3s.
[0087] D) Set the number of cycles to 750 and the effective deposition time to 150 s.
[0088] E) Remove the electrode, rinse with deionized water and ethanol, and dry.
[0089] Step 4: Sintering Process
[0090] A) The prepared electrode was placed on a mesh belt furnace, the sintering temperature was set to 1000°C, the sintering time was set to 1 s, and nitrogen was used as the protective atmosphere.
[0091] B) Place the electrode into a preheated 1000°C mesh belt furnace to ensure instant sintering.
[0092] C) After sintering, the electrode is taken out of the furnace after cooling to room temperature, and then washed with deionized water and dried.
[0093] Step 5: Performance Evaluation:
[0094] A) Material Characterization
[0095] Morphology observation: Scanning electron microscopy (SEM) was used to evaluate the changes in the surface morphology of the material and observe the morphology changes caused by cerium doping.
[0096] Surface analysis: The electrode surface is analyzed using energy dispersive X-ray spectroscopy (EDS) to confirm the successful introduction of the target elements and their chemical state.
[0097] B) Performance Evaluation:
[0098] The test was performed using a three-electrode system, with the electrode prepared in this example as the working electrode, the mercuric oxide electrode as the reference electrode, and the graphite electrode as the counter electrode.
[0099] The test was carried out in a 1M KOH aqueous solution. The electrolyte was fully saturated with oxygen before the test to ensure that the oxygen concentration in the electrolyte was constant during the test.
[0100] Linear Sweep Voltammetry (LSV) Test:
[0101] LSV tests were performed to evaluate the oxygen evolution reaction (OER) activity of the materials at a scan rate of 5 mV / s in the range of 0 V to 0.8 V vs. mercuric oxide.
[0102] Electrode performance test LSV curve Figure 3 As shown, it can be seen that after the introduction of Ce element, the electrode performance is greatly improved.
[0103] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A method for preparing a high-performance catalytic electrode material for hydrogen production by water electrolysis, characterized in that: The following steps are involved: S1. Substrate pretreatment: pretreating the conductive substrate to remove surface impurities; S2. Preparation of electroplating solution: prepare an electroplating solution including a nickel source, a pore-forming agent, an iron source, and a cerium source, wherein the nickel source is a nickel salt compound providing nickel ions, and the concentration is in the range of 0.1M to 1M, the pore-forming agent is a compound that generates gas to assist pore formation during electrolysis, and the concentration is in the range of 0.5M to 4M, the iron source is a ferric salt compound providing ferrous ions, and the concentration is in the range of 0.1M to 0.5M, and the cerium source is a cerium salt compound providing cerium ions, and the concentration is in the range of 0.1M to 0.5M; S3, electrodeposition process: using the electroplating solution obtained in S2, the pretreated conductive substrate is used as a cathode, another conductive material is used as an anode, and electrodeposition conditions are applied by a power supply to perform electrodeposition; S4, post-treatment: After the electrodeposition is completed, the electrode is taken out from the electrolyte, rinsed with a cleaning solution to remove the residual electrolyte on the surface, and then dried; S5. Sintering process: Sintering the electrode under a protective atmosphere to obtain a high-performance catalytic electrode material for hydrogen production by electrolysis of water.
2. The method for preparing a high-performance catalytic electrode material for hydrogen production by water electrolysis according to claim 1, characterized in that: In S1, the pretreatment includes ultrasonic cleaning with an acidic solution, ultrasonic cleaning with deionized water, and ultrasonic cleaning with anhydrous ethanol in sequence, followed by drying.
3. The method for preparing a high-performance catalytic electrode material for hydrogen production by water electrolysis according to claim 1, characterized in that: In S2, the nickel source is one of nickel sulfate, nickel nitrate and nickel chloride.
4. The method for preparing a high-performance catalytic electrode material for hydrogen production by water electrolysis according to claim 1, characterized in that: In S2, the pore-forming agent is ammonium chloride, which is used to form a bubble template to achieve pore formation.
5. The method for preparing a high-performance catalytic electrode material for hydrogen production by water electrolysis according to claim 1, characterized in that: In S2, the iron source is ferrous chloride, and the cerium source is cerium chloride or cerium nitrate.
6. The method for preparing a high-performance catalytic electrode material for hydrogen production by water electrolysis according to claim 1, characterized in that: In S3, when the three elements Ni, Fe, and Ce are deposited in one step, during the electroplating process, the pretreated nickel mesh is used as a cathode, connected to a negative power supply, and a nickel rod is used as an anode, connected to a positive power supply, and a constant voltage is applied by the power supply for electroplating, the applied voltage is 1V to 10V, the electroplating time is controlled at 5 to 30 minutes, and the temperature is controlled at 20°C to 60°C; The electroplating solution is a mixed electroplating solution prepared with a nickel source, a pore-forming agent, an iron source, and a cerium source according to a preset concentration; When depositing the three elements Ni, Fe, and Ce in one step, the mixed electroplating solution of the nickel source, pore former, iron source, and cerium source needs to be stirred evenly and left to stand for 10-30 minutes after preparation to ensure that each component is fully dissolved and evenly dispersed.
7. The method for preparing a high-performance catalytic electrode material for hydrogen production by water electrolysis according to claim 1, characterized in that: In S3, a two-step deposition method is used to introduce only Ce element into the nickel-iron porous electrode on the electrode surface. The electrodeposition process includes: In the two-step deposition, when the nickel-iron porous electrode is only introduced with the Ce element on the electrode surface, the following steps are included: 1) Preparation of nickel-iron electrode substrate: During the electrodeposition process, the pretreated nickel mesh is used as the cathode and connected to the negative power supply; the nickel rod is used as the anode and connected to the positive power supply. A constant current is applied through the power supply for electrodeposition, and the current density is 0.5A / cm 2 Up to 2A / cm 2 , the electrodeposition time is controlled within 5 to 30 minutes, and the temperature is controlled within 20°C to 60°C; The electroplating solution is a mixed electroplating solution containing a nickel source, a pore-forming agent, and an iron source prepared at a preset concentration; 2) Deposition of nickel-iron-cerium on a nickel-iron substrate: During the electroplating process, the pretreated nickel mesh is used as the cathode, connected to the negative power supply, and the nickel rod is used as the anode, connected to the positive power supply. A constant voltage is applied by the power supply for electroplating, and the applied voltage is 1V to 10V. The electroplating time is controlled within 5 to 30 minutes, and the temperature is controlled within 20°C to 60°C. The electroplating solution is a mixed electroplating solution prepared by mixing nickel source, pore-forming agent, iron source and cerium source at preset concentrations, wherein the nickel source is one of nickel sulfate, nickel nitrate or nickel chloride.
8. The method for preparing a high-performance catalytic electrode material for hydrogen production by water electrolysis according to claim 7, characterized in that: In S3, during the preparation of the nickel-iron electrode substrate, the electroplating solution used must first be prepared to completely dissolve the nickel source and the pore-forming agent, and then the iron source is added and continuously stirred until the solution is clear and transparent.
9. The method for preparing a high-performance catalytic electrode material for hydrogen production by water electrolysis according to claim 7, characterized in that: In S3, during the deposition of nickel-iron-cerium on the nickel-iron substrate, the electroplating solution is continuously stirred during the electrodeposition process at a stirring speed of 200-500 rpm to ensure uniformity of the electrodeposition.
10. A high-performance catalytic electrode material prepared by the method according to any one of claims 1 to 9, characterized in that: The catalyst improves the catalytic performance and stability of the electrode through a large number of oxygen vacancies provided by the redox couple of Ce, promotes the OER reaction and the formation of oxygen, and thus accelerates the process of hydrogen production by electrolysis of water.
Citation Information
Patent Citations
Rare earth-zinc-nickel multi-element alloy anti-corrosion anti-fatigue electroplating liquid for metal surface as well as preparation method of electroplating liquid
CN109161940A
Method for preparing self-supporting three-dimensional bifunctional catalytic electrode with porous structure
CN110205636A
Self-supporting alkaline electrolytic water hydrogen production electrode with gradient pore structure as well as preparation method and application of self-supporting alkaline electrolytic water hydrogen production electrode
CN116334679A
Aqueous electrodeposition of rare earth and transition metals
US6306276B1
Nickel-based alloy composite electrode having gradient component structure, and preparation method therefor and use thereof
WO2024021403A1
Cited By
Preparation method of nickel-iron-based oxygen evolution reaction catalyst with uniform phase based on micro-area primary battery
CN121381050A
Electrode for hydrogen production through water electrolysis and preparation method and application thereof
CN122484806A